2009
DOI: 10.2478/v10006-009-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Verification Techniques for Sensitivity Analysis and Design of Controllers for Nonlinear Dynamic Systems with Uncertainties

Abstract: Control strategies for nonlinear dynamical systems often make use of special system properties, which are, for example, differential flatness or exact input-output as well as input-to-state linearizability. However, approaches using these properties are unavoidably limited to specific classes of mathematical models. To generalize design procedures and to account for parameter uncertainties as well as modeling errors, an interval arithmetic approach for verified simulation of continuoustime dynamical system mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The rank of Q(x) yields sufficient information about the dimension of the observable manifold of the dynamical system [33,35,36].…”
Section: (T) Of Open-loop Controllers (S Is Open Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The rank of Q(x) yields sufficient information about the dimension of the observable manifold of the dynamical system [33,35,36].…”
Section: (T) Of Open-loop Controllers (S Is Open Inmentioning
confidence: 99%
“…First, uncertainties and robustness requirements can be expressed directly in the constraints (18). In addition, the verified approach can also handle differentially non-flat systems if stability of the internal dynamics can be guaranteed [32,33]. For most of these non-flat systems, the output y(t) does not coincide exactly with y d (t).…”
Section: (T) Of Open-loop Controllers (S Is Open Inmentioning
confidence: 99%
“…Using techniques for symbolic formula manipulation, it can be shown that the observability mapping (Rauh et al, 2009;Isidori, 1995) contains additional information that is not present in the cases in which the system model is linearized first. Moreover, the Jacobian of this observability mapping is a matrix of full rank, corresponding to a sufficient criterion for local observability.…”
Section: Observer and Filter Designmentioning
confidence: 99%
“…Despite their widespread use in such areas as uncertainty quantification, experimental design, parameter estimation, optimization, and control, very little work has been devoted to set-valued integration for sensitivity analysis so far. In [39], the parametric ODEs and their first-order sensitivities are bounded as one combined set of ODEs. But more efficient staggered or simultaneous corrector methods have not been investigated in this context to date.…”
Section: A3015mentioning
confidence: 99%
“…The nonlinear term N ϕ k (resp., N η k ) is so chosen that (37) and (40) (resp., (39) and (41) Moreover, we shall assume for now that nonlinearity bounders Ω ϕ k (t), Ω η0 , Ω η k ∈ IR ny can be constructed such that…”
Section: Ellipsoidal Remainder Boundsmentioning
confidence: 99%